(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2007)
A total of thirty microsatellite molecular markers were used across 21 rice genotypes for their characterization and discrimination. The number of alleles per locus ranged from three (RM165, RM219, RM248, RM463, RM470 and RM517) to nine (RM223), with an average of 4.53 alleles across the 30 loci obtained in the study. The polymorphism information content (PIC) values ranged from 0.30 (RM219) to 0.84 (RM223) in all 30 loci. RM223 was found the best marker for the identification of 21 genotypes as revealed by PIC values. The frequency of the most common allele at each locus ranged from 24% (RM223 and RM334) to 81% (RM219). A two dimensional principal coordinate analysis (PCoA) with 21 genotypes showed that the genotypes Supper Basmoti, Basmati370, BasmatiD, Keora, Chinisakkora, Thakurbhog, Benaful, Kolgochi, Buchi, Awnedtapl and Kalijira-11 were found far away from centroid of the cluster than rest of the genotypes which placed around the centroid. The pair-wise genetic dissimilarity coefficients indicated that the highest genetic distance was obtained between Thakurbhog and Supper Basmoti (0.81) as well as between Benaful and Keora (0.81). Basmati (Basmoti D, Super Basmati, Basmati 370) and Kalijira (Kalijira 11, 12, 13, 14) genotypes had close similarity among them but showed wide dissimilarity with other local genotypes. Being grouped into distant clusters, SupperBasmoti, Thakurbhog, Keora, and Benaful could be utilized as potential parents for the improvement of fine grain aromatic rice varieties. Genotypes Kolgochi and Buchi (having zero dissimilairty) might be possessed same genetic background. The microsatellite marker based molecular fingerprinting could serve as a sound basis in the identification of genetically distant accessions as well as in the duplicate sorting of the morphologically close accessions. DOI: http://dx.doi.org/10.3329/bjpbg.v20i2.17028